Effectiveness of Virgin Coconut Oil in The Provision of Injury Pressure Sores Stroke Patients: Systematic Review - Sya'bani, Nurul Indah; Hafid, Muhammad Anwar; Putra, Andi Budiyanto Adi (Journal Of Nursing Practice, 2020)
Background: VCO is an oil made from fresh coconuts and processed naturally or do not require heating and do not add other chemicals. The fatty acids contained in the VCO has the added benefit of making your skin soft. VCO is effectively applied as a moisturizer to the skin so that it can improve skin hydration and promotes healing of the skin. Decubitus is damage to the skin caused by friction or pressure on the skin located bony section.Purpose: This literature review aimed to determine the effectiveness of the VCO in reducing the risk of decubitus sores.Method: This research method Quantitative descriptive approach Systematic Review through some journals that are relevant to this article. This research article search by using keywords 1 "prevention of decubitus sores" keyword 2 "VCO" search database sources used in this study is Portal Garuda, ISJD and Google Scholar were published from 2015 to 2019 year.Results: The results of this study identified include the use of VCO prevent decubitus sores, that VCO is effective in prevention of decubitus sores in patients with stroke or bedrest.The use of VCO as decubitus sores preventive therapy has many benefits. Substances that are contained in the VCO can provide benefits or nutrients to keep the skin moist.Conclusion: Nurses as nursing care providers are expected to use the VCO to prevent decubitus sores in patients with stroke or bedrest as an intervention in a hospital or as therapy can do at home community.